ETNOMATEMATIKA MASYARAKAT MALUKU TENGAH DAN KOTA AMBON: PEMIKIRAN MATEMATIKA DALAM MULTIKULTURAL - Patma Sopamena (MATEMATIKA DAN PEMBELAJARAN, 2016)
Ethnomatematics is a cultural approach mathematical thinking is shaped by multicultural community of mathematical objects. This study aims for exploration Etnomatematika Community Central Maluku and Ambon city: Thinking Mathematics in Multicultural. This research is classified ethnographic research with qualitative descriptive approach. The subject of research as much as three persons from the society and academia. Data in the form of interviews. The results show that that there are ways that are specific to the community of Central Maluku and Ambon city in doing math activities. Without studying the theory of mathematical concepts, the people of Central Maluku and Ambon City has also applied mathematical concepts in their daily lives using ethnomatematics. Proved their form ethnomatematics community Central Maluku and Ambon city is reflected through various activity results of mathematical owned and developed in the community of Central Maluku and Ambon city, covering math concepts on: (a) cultural legacy in the form of artifacts (logo / symbol Nunusaku) form geometric forms in parts of artifacts, including flat figure model, a circle, a model mathematical properties, including symmetry, and the concept of translation (shift), as well as dilatation pattern rectangle where the artifacts that make up the arithmetic progression. (b) motif woven village artisans Laimu Central Maluku district including the concept of circles, straight lines and curved lines, symmetric, reflection, scaling, translation and rotation. Key Words: ethnomatematics, community central maluku and ambon, thinking mathematics in multicultural.